Analisis Kualitas Pelayanan Publik di Kantor Desa Macanputih Kecamatan Kabat Banyuwangi - Nur Prasetyo (Universitas 17 Agustus 1945 Semarang, Indonesia, 2025)
The village government has an important role in providing direct services to the community, both administrative, social, and other services related to the daily needs of residents. The quality of public services is one of the main indicators in assessing the success of village government administration (Irawan, 2017). According to Parasuraman, Zeithaml & Berry (1988), service quality can be measured through five dimensions, known as the SERVQUAL theory, namely: Tangibles, Reliability, Responsiveness, Assurance and Empathy. This study uses a descriptive qualitative approach with a purposive sampling method. This study uses interactive data analysis according to Miles and Huberman which includes three stages: data reduction, data presentation and drawing conclusions/verification. The conclusion is that the quality of public services at the Macanputih Village Office is running quite well but not evenly distributed. The services provided by officers show good intentions and openness, but there are still some weaknesses, namely: Lack of adequate facilities and infrastructure, Delays in completing administrative services, Differences in attitudes and abilities between officers in responding to residents, and the absence of a clear service flow.